Understanding social work’s role in abortion care: A comprehensive scoping review - Preetika Sharma; Julie L. Halverson; Yoonhee Lee; Sarmitha Sivakumaran; Cam Bautista; Hajar Seiyad; Ayla Arhinson; Temulun Bagen; Gajathree Ananthathurai; Stephanie Begun (PLoS ONE, 2025)
Background Social workers have played a crucial role in abortion care for decades, addressing clients’ diverse abortion care needs. Social workers have ethical duties to provide unimpeded access to information and supports to clients, in pursuit of social justice. This scoping review comprehensively synthesizes published literature on social work’s role in abortion care. Methods The review adhered to Arksey and O’Malley’s five-stage framework. The following databases were searched for literature published between 1973–2023: PsycINFO, MEDLINE, CINAHL, Social Work Abstracts, Social Services Abstracts, and Scopus. Search results were uploaded to Covidence for de-duplication and screening. Out of 2,980 articles screened in title and abstract review, followed by full-text review, 78 articles were included. Results A majority the 78 studies (n = 67) were set in the United States. The remainder were from the United Kingdom, Australia, Canada, New Zealand, and two studies involved multiple countries. Six themes emerged to summarize the literature base: (1) Social workers’ attitudes regarding abortion and abortion-seekers; (2) Abortion stigma and barriers in social work; (3) Social work and reproductive justice; (4) Social work and ethical considerations regarding abortion; (5) Social work and abortion policy and advocacy; and (6) Social work and family planning: roles, approaches, and practice frameworks. Discussion Social workers have long played intrinsic roles in abortion care, including counseling, providing access to concrete supports and mitigating barriers to abortion care, and abortion rights advocacy. Social justice and professional ethical commitments underpin social work’s role in abortion care. However, existing gaps in abortion education, training, and practice frameworks are impeded by the dynamic legal landscape and stigma attached to people seeking abortion care. Reproductive justice offers a framework, that overlaps with the field’s social justice tenets, to raise consciousness among social work students, professionals, and researchers, and to address gaps in abortion education, training, and scholarship.